Effect Of Phyllanthus N/Ruri Extracts On High Fat Diet Induced Non-Alcoholic Fatty Liver Disease In Rats - Al Zarzour, Raghdaa (2017)
Non-alcoholic fatty liver disease (NAFLD), a multifactorial condition that can exacerbate into non-alcoholic steatohepatitis and liver cirrhosis, is the prime cause of chronic hepatic damage in patients with no history of alcohol consumption. It is strongly linked to insulin resistance, obesity and oxidative stress. Unfortunately, due to the lack of standard treatment for NAFLD, healthcare goals have only been to decrease the patient's weight, ameliorate oxidative stress and improve insulin resistance. This study investigated the therapeutic activity of Phyllanthus niruri (Euphorbiaceae), an herb traditionally used for the treatment of liver diseases in a number of Asian communities, against NAFLD.